2021
DOI: 10.1111/mpp.13050
|View full text |Cite
|
Sign up to set email alerts
|

Potato StMPK7 is a downstream component of StMKK1 and promotes resistance to the oomycete pathogen Phytophthora infestans

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…Among them, two of the five RNA-binding proteins ( Table S1 , see online supplementary material), StUBA2a/b and StUBA2c [ 30 ], are reported to trigger SA-related plant cell death (CD) in tobacco leaves, which is also observed in CA-StMPK7 expressing N . benthamiana leaves [ 35 ]. We thus selected StUBA2a/b as a potential target of StMPK7 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, two of the five RNA-binding proteins ( Table S1 , see online supplementary material), StUBA2a/b and StUBA2c [ 30 ], are reported to trigger SA-related plant cell death (CD) in tobacco leaves, which is also observed in CA-StMPK7 expressing N . benthamiana leaves [ 35 ]. We thus selected StUBA2a/b as a potential target of StMPK7 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that StMPK7 promotes plant immunity through SA-related immune signalling [ 35 ]. We thus determine whether UBA2a/b-mediated plant immunity depends on the SA signalling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that SA treatment increased the TaMAPK4 transcripts in wheat under an avirulent race of pathogen attack, whereas knockdown the TaMAPK4 gene downregulated the SA accumulation [ 219 ]. Meanwhile, StMKK1 protein negatively regulated SA-related signalling pathways in defence against pathogens in potato [ 220 ]. Mpk4 mutant accumulated excessive levels of SA, but this was not the reason for its extreme dwarf phenotype, as knocking down the ICS1 gene (SA synthesis) did not revert mpk4-impaired growth [ 221 ].…”
Section: Possible Mechanisms Of Sa In Mitigating Abiotic Stressesmentioning
confidence: 99%